Interleukin‐6 and the Risk of Adverse Outcomes in Patients After an Acute Coronary Syndrome: Observations From the SOLID‐TIMI 52 (Stabilization of Plaque Using Darapladib—Thrombolysis in Myocardial Infarction 52) Trial. Issue 10 (24th October 2017) - Fanola, Christina L.; Morrow, David A.; Cannon, Christopher P.; Jarolim, Petr; Lukas, Mary Ann; Bode, Christoph; Hochman, Judith S.; Goodrich, Erica L.; Braunwald, Eugene; O'Donoghue, Michelle L.
Abstract : Background: Interleukin‐6 (IL‐6) is an inflammatory cytokine implicated in plaque instability in acute coronary syndrome (ACS). We aimed to evaluate the prognostic implications of IL‐6 post‐ACS. Methods and Results: IL‐6 concentration was assessed at baseline in 4939 subjects in SOLID‐TIMI 52 (Stabilization of Plaque Using Darapladib—Thrombolysis in Myocardial Infarction 52), a randomized trial of darapladib in patients ≤30 days from ACS. Patients were followed for a median of 2.5 years for major adverse cardiovascular events; cardiovascular death, myocardial infarction, or stroke) and cardiovascular death or heart failure hospitalization. Primary analyses were adjusted first for baseline characteristics, days from index ACS, ACS type, and randomized treatment arm. For every SD increase in IL‐6, there was a 10% higher risk of major adverse cardiovascular events (adjusted hazard ratio [adj HR] 1.10, 95% confidence interval [CI] 1.01‐1.19) and a 22% higher risk of cardiovascular death or heart failure (adj HR 1.22, 95% CI 1.11‐1.34). Patients in the highest IL‐6 quartile had a higher risk of major adverse cardiovascular events (adj HR Q4:Q1 1.57, 95% CI 1.22‐2.03) and cardiovascular death or heart failure (adj HR 2.29, 95% CI 1.6‐3.29). After further adjustment for biomarkers (high‐sensitivity C‐reactive protein, lipoprotein‐associated phospholipase A2 activity, high‐sensitivity troponin I, and B‐type natriuretic peptide), IL‐6 remained significantly associated with the risk of major adverse cardiovascular events (adj HR Q4:Q1 1.43, 95% CI 1.09‐1.88) and cardiovascular death or heart failure (adj HR 1.79, 95% CI 1.22‐2.63). Conclusions: In patients after ACS, IL‐6 concentration is associated with adverse cardiovascular outcomes independent of established risk predictors and biomarkers. These findings lend support to the concept of IL‐6 as a potential therapeutic target in patients with unstable ischemic heart disease.